2012
DOI: 10.1016/j.jqsrt.2012.07.022
|View full text |Cite
|
Sign up to set email alerts
|

Modifications of discrete ordinate method for computations with high scattering anisotropy: Comparative analysis

Abstract: A numerical accuracy analysis of the radiative transfer equation (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…In order to speed-up computations, modern RT codes truncate the scattering function and apply single (or sometimes double) scattering correction 29 as post processing. Our experience 30 showed that such an approach gives huge errors in the aureole area. Because we are planning to use the code for observations from ground, we refrained from using any truncation technique 31 until further detailed research.…”
Section: Features Of the Codementioning
confidence: 95%
“…In order to speed-up computations, modern RT codes truncate the scattering function and apply single (or sometimes double) scattering correction 29 as post processing. Our experience 30 showed that such an approach gives huge errors in the aureole area. Because we are planning to use the code for observations from ground, we refrained from using any truncation technique 31 until further detailed research.…”
Section: Features Of the Codementioning
confidence: 95%
“…The code was extensively tested using 52 benchmark scenarios providing an accuracy of ∼ 0.1 % for both intensity and polarization calculations. Unlike V2 RTC, whose speed was boosted by employing the truncation approximation of Nakajima and Tanaka (1988), no such approximation is used by SORD due to the potential problems it can cause in the forward scattering direction (e.g., Korkin et al, 2012). The NASA Center for Climate Simulation (NCCS) at the NASA Goddard Space Flight Center (GSFC) Discover cluster is utilized to overcome the significant increase in computational resources required for the application of SORD in AERONET retrievals (https://www.nccs.nasa.gov/ systems/discover, last access: 8 June 2020).…”
Section: Version 3 Retrieval Algorithm Descriptionmentioning
confidence: 99%
“…Single scattering path radiance and reflection of the direct solar beam from the surface are computed analytically. In order to avoid errors in the aureole (Korkin et al, 2012), none of the phase function truncation techniques (Rozanov and Lyapustin, 2010) has been implemented so far. IPOL ignores atmospheric curvature, 3D effects, and thermal emission.…”
Section: Ipolmentioning
confidence: 99%